2019
DOI: 10.3389/fpsyg.2019.00733
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Primary School Children’s Creative Potential Through Dynamic Assessment

Abstract: This paper focused on examining primary school students’ creative potential (CP) through dynamic assessment (DA). The study was carried out through a quasi-experimental design. The sample consisted of 90 Greek primary school students between fourth and sixth grade who were randomly divided into a group that received DA ( N = 37) and a control group ( N = 53). Both groups were initially tested with the graphic-artistic form of the Evaluation of Potential Creativity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The result testifies the third study question, for the teacher mediates as interventionist and interactionist to improve learning by providing sequential prompts. Rashidi and Najed (2018), Adeline (2012), Dimitrios and Athanasia (2019), recommend this tendency. As per the results, 59.1% of respondents agreed with devoting instructional time during classes to fill learning gaps, and 56.8% of respondents preferred giving all the instructions at a time for a specific task.…”
Section: Interview Protocolmentioning
confidence: 99%
“…The result testifies the third study question, for the teacher mediates as interventionist and interactionist to improve learning by providing sequential prompts. Rashidi and Najed (2018), Adeline (2012), Dimitrios and Athanasia (2019), recommend this tendency. As per the results, 59.1% of respondents agreed with devoting instructional time during classes to fill learning gaps, and 56.8% of respondents preferred giving all the instructions at a time for a specific task.…”
Section: Interview Protocolmentioning
confidence: 99%
“…Other studies have indicated divergent thinking to be a better predictor for academic success than intelligence measures [44,45], possibly due to the relationship between divergent thinking and extrinsic motivation. The application of dynamic testing to divergent thinking is still limited, but research has nevertheless demonstrated that it could be successful [46,47]. These studies have indicated that training during dynamic testing improves divergent thinking, and that dynamic measures can be used to identify different types of learning styles.…”
Section: Reasoningmentioning
confidence: 99%
“…DA is highly usable in classrooms and other settings where digital platforms are available, and is also applicable for assessing the current and future performance of children with special needs, de ned variously as their neurodevelopmental pro le (Naranjo and Robles-Bello, 2020), educational trajectories (Cho et al, 2020) or developmental circumstances (Henderson, Restrepo and Aiken, 2018). Working with children with special needs or whose language is not that of the static assessments, DA can evaluate current educational skills and construct a child's ZPD (Zbainos and Tziona, 2019). It has been argued that DA is better than static assessment tasks (Petersen et al, 2020), it can predict educational trajectories (Petersen, Gragg and Spencer, 2018) and can support the design of useful interventions (Feuerstein et al, 2019).…”
Section: Dynamic Assessmentmentioning
confidence: 99%